PENGARUH SIKAP, NORMA SUBJEKTIF, DAN PERSEPSI KONTROL KEPERILAKUAN, TERHADAP NIAT SISWA SMK DI KOTA DENPASAR UNTUK MENJADI WIRAUSAHA - Mirawati, Ni Made; Wardana, I Made; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
ABSTARCT The purpose of this study is to analyze the effect of entrepreneurs attitudes, subjective norms, and perceived behavior control towards the intention of being entrepreneurs. Respondents in this study were the twelfth grade students of Vocational High School in Denpasar. The sample used were 100 students by utilizing purposive sampling method. The research instruments udes questionnaires and analysis techniques used multiple linear regression analysis. The result showed that the attitude, subjective norms, and perceived behavior control effect positively and significantly towards the intention of being entrepreneurs. It is suggested to the school  to hold seminars by inviting success young entrepreneurs which can be an inspiration to the students in order to enchange students positive attitude towards the profession of entrepreneurial. Parents encouragement is needed to support students intention to be entrepreneurs. In learning process, it should be concrete efforts of the teachers to establish leadership which is one of persons principle to become entrepreneur. For the further research, it is suggested to add the background of parents occupation and cultural background  which can influence the intention of students to be entrepreneur.
Keywords: entrepreneur attitudes, subjective norm, perceived behavior control, intention of being entrepreneur